Why do people give to their governments? Lab-in-the-field evidence on the role of norms, social information, and political support - López Pérez, Raúl (2024)
Although factors leading to selfless acts, such as charitable donations, have been a central concern in political sciences, voluntary donations are among the most atypical and less well-known public revenue-raising sources. In this article, we explore which factors influence people's donations to their government. We conduct an artefactual field experiment in Peru where subjects anonymously decide how much of an endowment they freely donate to the government. We run six sessions with a sample that is representative of the taxpayer population of Metropolitan Lima regarding age, gender, and socioeconomic conditions. Our results suggest that donations depend on the subject's support to the government, the average donation by other subjects (social information) and their beliefs about the average donation of others (perceived social norms).